A novel E6-like gene, E6-2, affects fruit ripening in tomato. (December 2021) - Kang, Jing; Gong, Jun; Zhang, Lincheng; Gao, Zihan; Xie, Qiaoli; Hu, Zongli; Chen, Guoping
Highlights: Silencing of E6 - 2 resulted in delayed fruit ripening. E6 - 2 influences total carotenoids and lycopene accumulation in fruit ripening. E6 - 2 affects ethylene sensitivity and multiple metabolisms. MADS-RIN directly activates the expression of E6 - 2 . Abstract: Tomato fruit ripening is a complicated and well-coordinated process with numerous metabolic changes resulted from endogenous hormone and genetic regulators. Although the regulation of MADS-box transcription factor (MADS-RIN) controlling fruit ripening has been widely reported, its mechanisms underlying need to be further improved. Here, we characterized a novel tomato E6-like gene, E6 - 2, whose transcripts showed a high accumulation in fruit ripening stages (Breaker, Breaker+4 and Breaker+7), but a low level was observed in Never ripe ( Nr ) and ripening inhibitor ( rin ) mutants. MADS-RIN directly activates the expression of E6 - 2 in vivo . Additionally, a remarkable reduction of E6 - 2 was observed in wild-type (WT) tomato fruits at the MG stage treated with 1-MCP. RNAi-mediated silencing of E6 - 2 resulted in delayed fruit ripening, reduced accumulation of the total carotenoid and lycopene, reduced content of ethylene production, and increased contents of the total pectin, cellulose, starch and soluble sugar. Moreover, the expression of carotenoid biosynthesis genes ( PSY1, PDS and ZDS ), ripening-related genes ( CNR, PG and ERF4 ), ethylene biosynthesis genes ( ACS2, ACO1 and ACO3 ), ethylene-responsive genes ( E4 and E8 ) and cell wall metabolism genes ( TBG4, PL, EXP1 and XTH5 ) were inhibited in E6 - 2 -RNAi lines. These results indicate that E6 - 2 plays an important role in regulating tomato fruit ripening targeted by RIN.